Change in FVC and survival in chronic fibrotic hypersensitivity pneumonitis. Issue 4 (7th September 2017) - Gimenez, Andrea; Storrer, Karin; Kuranishi, Lilian; Soares, Maria Raquel; Ferreira, Rimarcs Gomes; Pereira, Carlos A C
Abstract : The predictive value of the decline in FVC by ≥10% on survival in patients with fibrotic hypersensitivity pneumonitis is unknown. Of 112 patients included, 66 (59%) had surgical lung biopsies. Patients with ≥10% decline in predicted FVC after 6–12 months had a significantly increased risk of all-cause mortality (median survival 53 months, 95% CI 37 to 69 vs 139 months, 95% CI 66 to 212 months, p=0.007). On multivariate analysis remained associated with increasing mortality: decline in FVC by ≥10% (HR 4.13, 95% CI 1.96 to 8.70, p=0.005), lower FVC% (HR 1.03, 95% CI 1.01 to 1.05, p=0.003) and with decreasing mortality improvement with antigen avoidance (HR 0.18, 95% CI 0.04 to 0.77, p=0.021).